The E3 ubiquitin ligase DTX3L and the deubiquitinase USP28 fine-tune DNA repair through mutual regulation of their protein levels - Daniela Mennerich; Yashwanth Ashok; Carlos Vela-Rodríguez; Heli I. Hentilä; Melanie Rall-Scharpf; Lisa Wiesmüller; Renata Prunskaite-Hyyryläinen; Lari Lehtiö; Thomas Kietzmann (iScience)
Summary: The DNA damage response (DDR) relies on a complex protein network to maintain genomic integrity, yet the interplay between post-translational modifiers remains poorly understood. Here, we uncover a novel regulatory axis between the E3 ubiquitin ligase DTX3L and the deubiquitinase USP28 at DNA double-strand breaks (DSBs). Our results reveal a sophisticated feedback mechanism in which DTX3L ubiquitinates USP28, leading to its proteasomal degradation, while USP28 counteracts by deubiquitinating both itself and DTX3L. This cross-regulation fine-tunes DSB repair in multiple pathways, including non-homologous end-joining (NHEJ), homologous recombination (HR), single-strand annealing (SSA), and microhomology-mediated end joining (MMEJ). Strikingly, the detrimental effects of USP28 depletion on these repair pathways were rescued by concurrent DTX3L knockdown. Collectively, our work uncovers a novel layer of DDR regulation in which DTX3L and USP28’s antagonistic activities calibrate cellular responses to genotoxic stress, thus identifying promising therapeutic targets to combat diseases associated with genomic instability.